Advancing educational excellence: International Conference on Quality Education in collaboration with AAPBS and UiTM - Bahrudin, Nur Zahidah (UiTM, 2023)
The international conference “Advancing Educational Excellence: International Conference on Quality Education”, organized in collaboration with AAPBS and UiTM, aimed to discuss best practices in quality education, strengthen international academic collaboration, and promote knowledge exchange among educators and researchers.